2000
DOI: 10.1001/archpedi.154.6.620
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analgesia and Local Anesthesia to Minimize Pain During Circumcision

Abstract: Infants circumcised with the Mogen clamp and combined analgesia have substantially less pain than those circumcised with the Gomco clamp and lidocaine-prilocaine cream. Because of the immense pain during circumcision, combined local anesthesia and analgesia using the Mogen clamp should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
2
30
0
1
Order By: Relevance
“…According to Taddio et al (2000) both acetaminophen and ketorolac are safe drugs regarding cardiac activity, respiratory function and temperature regulation. So findings in this study are consistent with their inference 26 . The safety status of intravenous ketorolac in neonates was ascertained principally on two variables: bleeding tendency and serum creatinine levels during postoperative period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to Taddio et al (2000) both acetaminophen and ketorolac are safe drugs regarding cardiac activity, respiratory function and temperature regulation. So findings in this study are consistent with their inference 26 . The safety status of intravenous ketorolac in neonates was ascertained principally on two variables: bleeding tendency and serum creatinine levels during postoperative period.…”
Section: Discussionsupporting
confidence: 92%
“…Efficacy was assessed principally by use of pain scoring (CRIES) and was found to be significantly low with ketorolac during all four postoperative days indicating better analgesic efficacy. According to Taddio et al (2000) regarding pain relief during operation, found Facial action scores and percentage of time spent crying were significantly lower during circumcision for infants in group who took ketorolac (P<.001) 26 . The percentage of time spent crying was 18% and 40% for infants in groups 1 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The combination of topical lidocaine-prilocaine with dorsal penile nerve block has been shown to be safe with less pain than topical lidocaine-prilocaine alone. 14 The utilization of topical lidocaine-prilocaine cream at the base of the penis prior to injection to reduce injection site pain during dorsal penile nerve blockade seems sensible, but has only been studied in older children undergoing circumcision. 19 Pain scores were similar when comparing reviewers with a medical background and those having no medical background.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral components have been videotaped for the investigators to complete analysis. [7][8][9][10][11][12][13][14] Video studies have only been reviewed by the study investigators and never reviewed by noninvestigators or by nonmedical persons. In addition, no studies have used sham procedures in comparing anesthesia techniques or evaluate baseline levels of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is important to consider the combination of various treatment modalities to maximize their analgesic effects and minimize the adverse effects or toxicity. 81 Perioperative Pain Nearly 1.4 million infants in the United States undergo operative procedures each year. 49 Pain management for these infants must include intraoperative and postoperative interventions.…”
Section: Procedural Painmentioning
confidence: 99%